Privacy in Participatory Research: Advancing Policy to support Human Computation (Human Computation, 2015)
Citizen science and participatory sensing are two models of human computation in which participant privacy is a key concern. Technological safeguards are important but partial solutions; a full and accurate description of policies explaining privacy practices must also be present so volunteers can make informed decisions regarding participation. Our study surveyed the policies of 30 participatory research projects to establish how privacy-related policies were presented, and how they aligned with actual practices. This paper contributes a description of the privacy-related elements of policies evident in these projects. We found that while the majority of projects demonstrated some understanding of the need for policies, many hosted incomplete policies or inaccurately described practices. We discuss the implications for project management, design, and research or operational policy, both for projects that self-categorize as citizen science or participatory sensing, and for the larger field of human computation. We conclude by proposing a set of Ethical Practices for Participatory Research Design as guidelines to inform the development of policies and the design of technologies supporting participatory research.
Keywords: Participatory Research; Citizen Science; Participatory Sensing; Data Policy; Privacy; Ethics